Subsurface Mapping of Fault Structure in The Weh Island by Using A 3D Density of Global Gravity - Abdullah, Faisal; Yanis, Muhammad; Razi, Muhammad Haikal; Zainal, Muzakir; Ismail, Nazli (GEOMATE International Society, 2022)
Indonesia's Aceh Province is an earthquake-prone area due to its location on the Great Sumatran Fault (GSF). Currently, earthquake mitigation by the local government constantly refers to the regional seismic hazard maps. However, some sources of an earthquake in the province which had caused damage to buildings and loss of human life were not easily traced to the fault on the surface. Currently, the mapping activities related to the Sumatra fault lines are only focused on the mainland. In contrast, the continuity of the GSF fault in the area of the sea and surrounding islands is very rarely studied. Weh Island is inhabited by many communities and has become a popular tourism area. This study aims to map the regional and local fault structure on the Weh Island using the gravity model plus (GGMPlus) data. We used the GGMPlus data with a resolution of 200 m for detailed mapping of regional and local faults. The 3D inversion of the GGMPlus data was carried out to obtain density parameters using two models, namely Singular Value Decomposition (SVD) and Occam optimization. The 3D inversion describes the presence of high-density rock blocks. A density value ranging between 2.72 - 2.96 gr/cm3 is interpreted as rocks with andesite-basaltic lava composition and lava or pyroclastic breccias resulting from local volcanic products as the rocks creating the island. Therefore, the zone interpreted as a local fault had a smaller density value (2.5 - 2.65 gr/cm3) than the surrounding. © 2022. Int. J. of GEOMATE All rights reserved, including making copies unless permission is obtained from the copyright proprietors.